Sistema remoto de automação residencial com recursos de computação em nuvem - Silva Neto, Francisco Ferreira da (2022)
Cloud Computing (CC) is a resource widely used in the Information Technology (IT) area, its implementation in a residential environment using the Internet of Things (IoT) concept can provide all the security, processing and stability of large CC services, as well as scalability and integration with other services such as database and mobile applications. This work aims to provide the user with remote control of home devices through a mobile application. To achieve this goal, it was necessary to use hardware and software resources integrated in a horizontal IoT architecture. Specifically, it was necessary to use AWS IoT as the main cloud service, the Android Studio IDE, the Zerynth framework and the development module ESP32, in addition to some sensors and actuators. In the end, a proposed architecture was fully implemented and with good stability in the exchange of information, thus enabling remote and online command in the electronics at result prototype.